Elsie Park Gowan's (re)-Building of Canada, 1937-1938: Revisioning the Historical Radio Series through Feminist Eyes - Day, Moira (Theatre Research in Canada / Recherches théâtrales au Canada, 1993)
Quite aside from its historical significance as one of the first prairie-generated series to reach national radio and as the definitive work that launched Gowan's career as a radio writer, Gowan's Building of Canada series (1937-38) raises a number of important questions about defining historicity within the context of historical dramatic writing. Where Merrill Denison, an often progressive writer of contemporary stage plays, chooses to celebrate the conventional values of male pioneer adventure, empire-building, war and military glory within the context of his seminal historical radio series, The Romance of Canada (1931), Gowan's Building represents a more complex attempt to reconcile her vision as a trained historian, concerned with the objective chronicling and analysis of the male-dominated world of wars, economy, politics and public life, with her vision as a social activist playwright committed to interpreting the human world through the focus of her socialistic, pacifistic and feminist convictions. Building of Canada de Gowan (1937-38): Laissons de côté son importance historique en tant qu'une des premières séries historiques venant des prairies à paraître à la radio nationale et en tant que l'oeuvre définitive qui a déclenché la carrière de Gowan comme écrivaine pour la radio. Cette série soulève beaucoup de questions importantes lorsqu'il s'agit de définir l'historicité dans le contexte de l'écriture dramatique et historique. Tandis que Merrill Denison, qui écrit d'une façon souvent progressiste des pièces de théâtre contemporaines, choisit de célébrer les valeurs conventionnelles des aventures des pionniers, de la construction d'un empire, de la guerre et de la gloire militaire dans le contexte de sa série séminale pour la radio. The Romance of Canada (1931), Building de Gowan représente une tentative plus complexe de concilier sa vision d'historienne diplômée, soucieuse de raconter et d'analyser le monde mâle des guerres, de l'économie, de la politique et de la vie publique, avec sa vision d'activiste sociale tenant à interpreter le monde human à travers ses convictions socialistes, pacifistes et féministes.